Do Extreme Weather Events Generate Attention to Climate Change? - Matthew R. Sisco; Valentina Bosetti; Elke U. Weber (Fondazione Eni Enrico Mattei (FEEM), 2016)
We analyzed the effects of 10,748 weather events on attention to climate change between December 2011 and November 2014 in local areas across the United States. Attention was gauged by quantifying the relative increase in Twitter messages about climate change in the local area around the time of each event. Coastal floods, droughts, wildfires, strong wind, hail, excessive heat, extreme cold, and heavy snow events all had detectable effects. Attention was reliably higher directly after events began, compared to directly before. This suggests that actual experiences with extreme weather events are driving the increases in attention to climate change, beyond the purely descriptive information provided by the weather forecasts directly beforehand. Financial damage associated with the weather events had a positive and significant effect on attention, although the effect was small. The abnormality of each weather event's occurrence compared to local historical activity was also a significant predictor. In particular and in line with past research, relative abnormalities in temperature (“local warming”) generated attention to climate change. In contrast, wind speed was predictive of attention to climate change in absolute levels. These results can be useful to predict short-term attention to climate change for strategic climate communications, and to better forecast long-term climate policy support.
Keywords: Q54; C81; D80; 330; Climate Attention; Social Media; Extreme Weather